Digital Control and Market Power in the Automotive Sector: OEMs, Gatekeeping, and the Future of Aftermarket Regulation - Florian Hey; Max Zombek (Journal of Industry, Competition and Trade, 2026)
The automotive industry is undergoing a fundamental transformation driven by digitization, enabling original equipment manufacturers (OEMs) to exert increasing control over vehicle functions, data, and – consequently – after-sales markets. Despite high relevance for consumers, regulatory scrutiny remains limited. This paper examines whether these developments constitute digital gatekeeping in a functional sense and whether they justify increased regulatory attention. We show that OEMs' digital strategies reinforce their dominance in secondary markets, particularly repair and maintenance. We assess the current European regulatory framework, focusing on the European Motor Vehicle Block Exemption Regulation (MVBER), and argue that it has not kept pace with the realities of software-defined vehicles. The planned MVBER review provides an opportunity to reassess legacy privileges and adapt competition rules to the digital age. We discuss potential reforms, including improved data access, stronger interoperability standards, and a broader definition of aftermarket components. We also examine supplementary measures such as a Right to Repair regime and self-regulation. Our analysis concludes that OEMs increasingly act as digital gatekeepers and that existing frameworks inadequately address the resulting risks. Regulatory recalibration is needed to safeguard innovation, consumer welfare, and long-term market openness.
Keywords: D72; K21; L40; L42; L50; L51; L62; 690; Aftermarket; Antitrust; Competition policy; Connected car; Extended vehicle; Gatekeeping; Software-defined vehicle